الرؤى الحديثة للتنمية القائمة على ادارة المعرفة تجارب نماذج مُختارة من الدول العالمية والعربية في بناء المجتمع المعرفي - جاسم, مريم العذراء سعد (Tasnim International Journal for Human, Social and Legal Sciences, 2023)
In today's world، knowledge occupies the forefront in various major activities and projects، because it is the key to every renaissance، and the main tributary for achieving comprehensive and sustainable development. For its citizens، and occupying a prominent place in the relevant global classifications، as well as (digital) and (knowledge).. two words that have newness and sweetness when they fall on the ears، as they represent two main pillars in building a knowledge-based society and economy، and in the background lies the Internet with its repercussions However، the shift from an information-based society at the end of the twentieth century to a knowledge-based society at the beginning of the current century came as a result of radical changes in many aspects of society's activities. Business، trade، industry، economy، politics، education and research، especially in the way information is employed، ways to solve dilemmas، and ways to search for answers to existing or emerging questions.